Mixed halide – hybrid perovskite via ambient reflux method insight into structural, chemical and optical properties of 2D hybrid perovskite with difference concentration of halidic acid / Nurul Shazwani Ezzati Badrul Hisham - Badrul Hisham, Nurul Shazwani Ezzati (2022)
Recently, numerical simulation of hybrid perovskite solar cells has attracted scientific community and received great attention. Hybrid organic–inorganic perovskite materials have promising electro-optical properties such as broad optical absorption coefficients, long electron–hole diffusion lengths, high charge carrier mobilities and potentially low fabrication cost. They are also relatively easy to process. These properties have contributed to making hybrid organic–inorganic perovskites promising candidates for next-generation, low-cost solar cell absorbers. Among organic–inorganic perovskite solar cell (PSC) materials, methylammonium lead iodide (CH3NH3PbI3 or MAPbI3), is used as light harvester.It has an ABX3 structure (A is organic cation, B is divalent metal cation and X is halogen ion), and can be vapor and solution processed into perovskite solar cells (PSCs) which favourably compares to established photovoltaic (PV) technologies. However, their stability and durability are limited, especially when exposed to air and moisture. In an effort to improve the stability and durability of MAPbI3 perovskite solar cells, new materials compositions have emerged. Moreover, perovskites with mixed halide compositions demonstrate attractive optical properties as the bandgap is tuned by varying the halide ion ratio (Cl:Br and Br:I). Next, in this thesis, we describe how hybrid perovskite based solar cells has become an important renewable source of energy along with historical background and the future of this potential material. We also describe the synthesis and fabrication methods for preparing ultrathin to bulk perovskites and their crystallographic nature of pure and mixed hybrid perovskite system. This review not only focused on properties of hybrid perovskite but also represents the drawback as well as the development and performance in different fields of application.